SORCERY AND ITS MENACE AMONG MUSLIMS: ISLAMIC DA'WAH IN PERSPECTIVE - Yahaya Sulaiman; Muhammad Maga Sule (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2023)
This paper is a contribution and a piece of Da'wah towards enlightening Muslims on the menace of sorcery and sorcerers. The work has highlighted some of the major reasons why some Muslims with weak Iman seek the help of sorcerers for worldly things thereby harming their fellow being. It is therefore, the application of Islamic Da’wah that would assist in reminding Muslims in avoiding the menace of sorcery. It has been discovered from the interview that sorcerers have destroyed many family relationships and created damage to some marriages, also economic backward to sorcery goers. The paper also found out that some sorcery goers do regret their actions after coming in contact with the truth. This study was conducted using a survey method, and data were collected through in-depth interviews. The results of this study showed the need for a sustainable Da'wah to combat the issue of sorcery and sorcerers that have become a menace among Muslims which have affected their Iman. The study recommended that there was an urgent need for engagement of various stakeholders in Nigeria and beyond, to checkmate the issue of sorcerers and their activities in the society.